2022
DOI: 10.18176/jiaci.0752
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Adherence to Treatment in Nasal Polyposis

Abstract: Chronic rhinosinusitis with nasal polyps (CRSwNP) is an inflammatory respiratory disorder with a significant deleterious impact on quality of life. Intranasal corticosteroids (INCS) and saline irrigation are the mainstay treatment [1].

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…This emphasizes the need to instruct patients on the proper application technique, which is routinely performed by roughly half of the participants in this survey. This is relevant since side effects may also reduce compliance to therapy [ 18 , 19 ]. Moreover, the correct use of topical steroids guarantees higher efficacy of the drug, which reaches the nasal polyps instead of the nasal septum or pharynx.…”
Section: Discussionmentioning
confidence: 99%
“…This emphasizes the need to instruct patients on the proper application technique, which is routinely performed by roughly half of the participants in this survey. This is relevant since side effects may also reduce compliance to therapy [ 18 , 19 ]. Moreover, the correct use of topical steroids guarantees higher efficacy of the drug, which reaches the nasal polyps instead of the nasal septum or pharynx.…”
Section: Discussionmentioning
confidence: 99%
“…Our results showed that INCS (88.3%) and oral antihistamines (51.8%) were the most prescribed drugs in CRSwNP patients. However, poor compliance of INCS has been previously reported in these patients (57) .…”
Section: Moreover Crs Patients Commonly Suffer From Coexisting T2mentioning
confidence: 72%